Answer:
228 and 222
Step-by-step explanation:
You can multiply or divide one equation so that it has a variable with a coefficient opposite of the other equation.
Example:
A) 2x + 3y = 6
B) 4x +2y = 20
Notice that neither equation has a "1" or "-1"
Let's multiply Equation A) by -2
A) -4x -6y = -12 Then add it to B)
B) 4x +2y = 20
-4y = 8
y= -2
A) 2x + 3*-2 = 6
2x = 12
x = 6
Answer: The correct answer is <em>-x+3y=6</em>
Step-by-step explanation:
<u>Solve for x:</u>
y=1/3x+2
1) Flip the equation:
1/3x+2=y
2) Add -2 to both sides:
1/3x+2+−2=y+−2
1/3x=y−2
3) Divide both sides by 1/3:
(1/3x)/(1/3)=(y−2)/(1/3)
x=3y−6
In standard form (Ax=By=C): -x+3y=6
Quadratic in equality is quadratic function that is compared to another function like: x^2+4x-1<2x-3. the answer for x must comply to both sides.